Design and Methodology of a Real Estate Fund Index for the Czech Market - Černohorský, Adam (ACTA VŠFS)
Background: The Czech real estate market has experienced rapid growth in recent years, driven by macroeconomic trends and limited housing supply. Retail investors face increasing barriers to direct property ownership, prompting a shift toward real estate investment funds (REIFs). However, the lack of a standardized performance benchmark hinders market transparency and comparability. Objective: This study aims to design a dual-index framework to benchmark the performance of Czech real estate investment funds. It investigates how fund structure, size, and investor segmentation affect index behaviour and evaluates the implications of different methodological approaches. Methods: Two types of indices, arithmetic and NAV-weighted, were constructed separately for retail and qualified investor funds. Data were collected quarterly from 39 real estate funds, with inclusion based on data availability and reporting consistency. Indices were computed using Python-based time-series processing, with quarterly rebalancing and weight capping to reduce concentration risk. Results: Qualified investor funds achieved higher average returns and exhibited lower performance dispersion. In contrast, retail funds displayed greater heterogeneity, and the weighted index was strongly influenced by a single large, underperforming fund. The arithmetic index proved sensitive to outliers, while the weighted index highlighted capital concentration effects. Recommendation: Investors and analysts should use both index types for a comprehensive performance view. Policymakers should encourage broader data disclosure and consider the systemic impact of dominant funds on retail benchmarks. Practical relevance: The indices provide a transparent benchmarking tool for market participants, enabling better performance evaluation and investment decision-making. The framework also supports regulatory efforts to enhance market maturity. Originality/value: This study is the first to introduce a dual real estate fund index for the Czech market. It provides an analytically sound and practically applicable model for benchmarking performance across investor segments, with methodological insights relevant to other emerging real estate markets.